The journal of medieval military history. - Bachrach, Bernard S., 1939-; Rogers, Clifford J.; DeVries, Kelly, 1956- (The Journal of Medieval Military History, 2002)
A new annual volume of original articles on all aspects of warfare in the middle ages.